The Validity of Receipts as Transactions for the Transfer of Land Rights Before the Law - Ahmadi, Ahmadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The large number of people who do not understand the law on land transfer rights has become a problem for the legal compliance of land rights owners. People who occupy or own land whose ownership is based only on receipts and private deeds become a problem that arises in the future. Legal certainty regarding the sale and purchase transaction in the transfer of land rights agreed between the seller and buyer based on a receipt without a Sale and Purchase Deed made by a PPAT or PPATS has not been registered at the Land Office, but many buyers still carry out sales and purchases without using a Sale and Purchase Deed made by a PPAT or PPATS. Buyers of sales and purchases carried out without using a Sale and Purchase Deed made by a PPAT and/or PPATS may face legal consequences, such as being unable to register the transfer of land rights at the local land office or not being able to have the land rights transferred to their name. Buyers who carry out sales and purchases that do not comply with procedures will be subject to legal sanctions for committing a violation of the law, either intentionally or due to carelessness in fulfilling their legal responsibilities. Negligent or wrongful acts result in the creation of incorrect legal certificate products, including errors in the legal subject or object of the certificate. As a result, the certificate becomes invalid at the time of its creation or cannot be processed. Legal protection for buyers in good faith can be done through special efforts by filing a lawsuit with the District Court to obtain legal certainty regarding ownership of land rights, then submitting a name change at the National Land Agency, then being able to record the transfer of rights to land ownership based on the decision taken in the lawsuit and used as support for the name change application.